Liposomal formulations for lung cancer treatment in the last two decades: a systematic review - Canão, Filipa (2022)
Purpose Lung cancer is the leading cause of cancer mortality worldwide. To improve the therapeutic outcomes, drug delivery systems, and particularly liposomes, have been widely investigated. Therefore, this review analyzed systematically the literature to inquire about the safety and efcacy of liposomal formulations in lung cancer treatment. Methods Three electronic databases (PubMed, Web of Science and Cochrane CENTRAL) were systematically searched until May 2020. Clinical trials containing information about the efects of liposomal formulations in lung cancer patients were considered eligible. Results Twenty two selected studies present diferent treatment options for both small and non-small-cell lung cancers. After compiling and analyzing all the published information, we verifed that combination of liposomal cisplatin and paclitaxel led to a statistically signifcant improvement of the evaluated outcomes. Moreover, tecemotide, a liposome-based immunotherapy, demonstrated lower toxicity compared to control groups. Evidences that other subgroups could beneft from this formulation were also provided. Conclusion This systematic review (registration number CRD42021246587) demonstrates that liposomal formulations are promising alternatives to overcome limitations of traditional cancer therapy. However, larger, longer, randomized and double-blinded clinical trials, selecting their patientsâ cohort considering more responsive subgroups would be benefcial to strengthen the scientifc and clinical evidence of the results herein reported.